The correspondence of Jean Sibelius and Rosa Newmarch, 1906-1939 - Sibelius, Jean, 1865-1957 (Boydell Press, 2011)
Rosa Harriet Newmarch [1857-1940] was well-known in her lifetime as the leading British authority on Russian music, yet she also enjoyed a long and close friendship with the Finnish composer, Jean Sibelius [1865-1957]. This edition traces a personal and professional relationship that lasted more than three decades, as documented in more than 130 letters, notes and telegrams currently held in the National Archives of Finland. The correspondence, conducted in a mixture of French and German, reveals the intense friendship between Sibelius and Newmarch, sheds detailed light on Newmarch's contribution to the development of musical life in Britain, and provides some of Sibelius's most intimate commentary on his own works, as well as on those of other composers. This edition contains the complete extant correspondence between Newmarch and Sibelius in English translation, complemented by comprehensive commentaries on the events and personalities referred to, and is prefaced by an extensive introduction outlining Newmarch's definitive role in promoting Sibelius and his music in early twentieth-century Britain. An appendix reproduces a previously unknown programme note that Newmarch wrote for the first British performance of Sibelius's Fourth Symphony. The book's translation and publication of the letters in English is complemented by the letters' online availability in their original language. PHILIP ROSS BULLOCK is University Lecturer in Russian at the University of Oxford, and Tutor and Fellow at Wadham College, Oxford.